Study of Heat-Recovery Systems for Heating and Moisturing Combustion Air of Boiler Units - Fialko, N.M.; Navrodska, R.O.; Gnedash, G.O.; Presich, G.O.; Shevchuk, S.I. (Наука та інновації, 2020)
Introduction. One of the ways to save natural gas and to improve the environmental conditions in the municipal heat-power engineering is to use progressive technologies for recovering the heat of flue gases from boiler plants, in which the condensation mode of operation of heat-recovery equipment is implemented. To increase the ecological effect in some heat-recovery systems, a humidification process of the combustion air occur. This lowers the combustion temperature of the fuel and reduces the concentration of nitrogen oxides in the combustion products. Problem Statement. At humidifying combustion air, the boiler exhaust-gases are characterized by high moisture content. In the known calculation methods, there are no data on heat transfer under these conditions. This is a problem for conducting thermal calculations of such installations. Purpose. Establishing patterns of heat transfer at an increased moisture content of exhaust-gases in heatrecovery equipment, consisting of bundles of transverse-finned pipes, and determining the main parameters of the proposed complex installation. Materials and Methods. Experimental studies of heat transfer were carried out on a specially created stand. For the thermal and hydraulic calculation of a heat-recovery installation, known calculation methods were used, taking into account the experimental data obtained. Results. The laws of heat transfer during deep cooling of exhaust-gases with moisture content X = 0.15—0.30 kg/kg d.g. are established. The thermal, hydraulic and operating characteristics of the proposed complex heat-recovery installation with heating and humidification of the combustion air in different modes of operation of the boiler are determined. This installation has been introduced; its tests have been carried out, which have confirmed high thermal and environmental efficiency. Conclusions. The application of the proposed complex heat-recovery unit allows increasing the coefficient of the use heat of fuel of boiler depending on its operating mode by 13—20%.